1998
DOI: 10.1007/s000180050252
|View full text |Cite
|
Sign up to set email alerts
|

CD100 is a leukocyte semaphorin

Abstract: CD100 was originally described as an activation molecule on the surface of human T lymphocytes. Its triggering through distinct epitopes leads to different signals of costimulation with phorbol myristate acetate (PMA) or with CD3 and CD2. Interestingly, CD100 was shown to associate with different partner molecules in T cells. First, CD100 can associate with CD45, a key molecule with protein tyrosine phosphatase activity involved in T-cell transduction: this association is physical and has functional consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 61 publications
0
87
0
2
Order By: Relevance
“…In the immune system, Sema4D is expressed in T cells, activated B cells and mature dendritic cells (DCs). 29,44,45 Sema4D promotes the activation of B cells and DCs to induce antibody production and antigen-specific T cells, respectively. 29,46,47 Plexin-B1 and CD72 were identified as the Sema4D receptors in the nervous and immune systems.…”
Section: Semaphorins and Their Receptorsmentioning
confidence: 99%
“…In the immune system, Sema4D is expressed in T cells, activated B cells and mature dendritic cells (DCs). 29,44,45 Sema4D promotes the activation of B cells and DCs to induce antibody production and antigen-specific T cells, respectively. 29,46,47 Plexin-B1 and CD72 were identified as the Sema4D receptors in the nervous and immune systems.…”
Section: Semaphorins and Their Receptorsmentioning
confidence: 99%
“…C D100 was initially identified using a pair of mAbs produced in our laboratory (1, 2) as a homodimeric human Ag expressed on most hemopoietic cells, except on immature CD34 ϩ cells, erythrocytes, and eosinophiles (3,4). Our previous studies showed that CD100 was an activation molecule on lymphocytes.…”
mentioning
confidence: 99%
“…CD100/SEMA4D foi a primeira semaforina caracterizada no sistema imune Hall et al 1996;Delaire et al, 1998), no qual possui um amplo espectro de atividades biológicas já descritas tanto no modelo murino como em humanos (Ishida et al, 2003). Evidências crescentes demonstram um importante papel de CD100 na imunidade humoral e celular Kikutani & Kumanogoh, 2003;Suzuki et al, 2008).…”
Section: Discussionunclassified
“…CD100 is the first human semaphorin described in the immune system Delaire et al, 1998). At the cellular level, human CD100 triggers costimulatory signals to T cells promoting their proliferation and priming (Herold et al, 1996), B cell survival, aggregation, antibody production and also cytokine secretion in response to T-dependent antigens , as well as enhancement of NK cells killing of target cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation